The 29-nucleotide deletion in SARS-CoV: truncated versions of ORF8 are under purifying selection - Bykova, Anastassia; Saura, Andreu; Glazko, Galina V; Roche-Lima, Abiel; Yurchenko, Vyacheslav; Rogozin, Igor B (BMC genomics, 2023)
BACKGROUND: Accessory proteins have diverse roles in coronavirus pathobiology. One of them in SARS-CoV (the causative agent of the severe acute respiratory syndrome outbreak in 2002-2003) is encoded by the open reading frame 8 (ORF8). Among the most dramatic genomic changes observed in SARS-CoV isolated from patients during the peak of the pandemic in 2003 was the acquisition of a characteristic 29-nucleotide deletion in ORF8. This deletion cause splitting of ORF8 into two smaller ORFs, namely ORF8a and ORF8b. Functional consequences of this event are not entirely clear. RESULTS: Here, we performed evolutionary analyses of ORF8a and ORF8b genes and documented that in both cases the frequency of synonymous mutations was greater than that of nonsynonymous ones. These results suggest that ORF8a and ORF8b are under purifying selection, thus proteins translated from these ORFs are likely to be functionally important. Comparisons with several other SARS-CoV genes revealed that another accessory gene, ORF7a, has a similar ratio of nonsynonymous to synonymous mutations suggesting that ORF8a, ORF8b, and ORF7a are under similar selection pressure. CONCLUSIONS: Our results for SARS-CoV echo the known excess of deletions in the ORF7a-ORF7b-ORF8 complex of accessory genes in SARS-CoV-2. A high frequency of deletions in this gene complex might reflect recurrent searches in "functional space" of various accessory protein combinations that may eventually produce more advantageous configurations of accessory proteins similar to the fixed deletion in the SARS-CoV ORF8 gene.
Keywords: Recombination; Gene regulation; otevřené čtecí rámce; Nucleotides; lidé; Protein truncation; Open Reading Frames; Natural selection; biologická evoluce; SARS-CoV-2; Biological Evolution; Evolution; nukleotidy; COVID-19; Rearrangements; Humans